PENGARUH TERAPI RELAKSASI BENSON TERHADAP INSOMNIA PADA USIA LANJUT DI KELURAHAN BONGAYA KOTA MAKASSAR - Mery Solon (Jurnal Keperawatan Florence Nightingale, 2019)
Elderly is a physiological process that cannot be avoided and will be experienced by everyone. In the elderly will experience a decrease in body function and various systems and one of them will affect the quality of sleep, which can cause changes in personality and behavior like. This study aimed to determine the effect of Benson relaxation therapy on insomnia in the elderly, the subjects were the elderly who experienced insomnia and lived in Bongaya Kelurahan Makassar. Sampling method with nonprobality sampling using consecutive sampling approach with the number of respondents 32 elderly who experienced insomnia based on Insomnia Rating Scale questionnaire, then given intervention in the form of Benson relaxation techniques every day for two weeks. Data were obtained by looking at the comparison of insomnia levels before and after the intervention using the Insomnia Rating Scale questionnaire. The data were then analyzed using the Wilcoxon sign rank test. This study showed that the value of p = 0.000 (p <?) so that it can be concluded that there was an influence of Benson Relaxation Therapy Against Insomnia In old age. From the research that has been done is expected that the elderly who experienced insomnia do Benson Relaxation Therapy well in order to overcome insomnia.